I’m a Chair, but I Feel Like a Therapist - Krista Bridgmon; Aaron Alexander; Elizabeth List (Academic Chairpersons Conference Proceedings, 2020)
For this seminar, we invite Chairs to evaluate situations in their practice that resemble the work of a counselor. To prime and contextualize this interactive workshop, the presenters will ignite the inner-listener. Skills in listening to listen, not listening to respond will be at the forefront of the presentation.
Keywords: Work-Life; faculty; leadership; counseling